Versatile offline simulation tool for systems design - Binet, L. (My University, 2021)
Abstract For dual pilot configuration, Active Side-Stick Units (ASSU) technology can provide intuitive tactile cueing in the cockpit. Through ASSU, haptic cueing is expected to be an efficient and intuitive communication mode with the crew, especially enabling to electronically couple two side-sticks. Considering new generation of active inceptors providing such functionalities, the EFAICTS (Ergonomic impact and new Functions induced by Active Inceptor integration in CockpiTS) project started in December 2018. This project has received funding from the Clean Sky 2 Joint Undertaking under the European Union’s Horizon 2020 research and innovation programme under grant agreement N° 820884, in which Safran Electronics & Defense is the Topic Leader and ONERA the project coordinator. The overall EFAICTS concept is to define, develop and validate new ergonomic information and new functionalities provided by ASSU to enhance crew coordination and autopilot understanding through coupling functions between active sticks, and between active sticks and the flight control system, and haptic feedbacks on sticks. In order to design and ease the integration of these developments in a real time simulator, an offline simulation tool has been set-up, suited to meet the goals of the EFAICTS project, but also enabling the development of any system that could be implemented in the ONERA's PycsHel simulation bench. The paper focuses on the development of this offline simulation tool and the possibilities it offers. A short description of the upgrades performed on the simulation bench are proposed before detailing the models and functionalities built in the offline loop to simulate the real environment and enabling the design and pre validation of all features needed in the framework of the EFAICTS project. Some comparisons between offline computations and real time simulations are shown, and the benefits of this offline tool highlighted. Finally, some future expected or already planned developments are described, demonstrating its high versatility and showing how this tool is fitted to system development and integration.